A Dashboard for Monitoring Opioids: Initiating and Assessing the Impact of Opioid Stewardship Programme in the Pain Management at Multispeciality Hospital in India - C, Dhandapani; K. S, Rajkumar; P, Lokesh; L, Madhumitha; C, Aravinth; S, Mohamed Sharif (Indian Journal of Pharmacy Practice)
Introduction: Pain affects 20% of adults globally and has an effect on their quality of life. Since 1999, the number of opioid overdose deaths has increased, leading to an opioid crisis. India’s opioid prevalence is three times the global average, with 2.1% of the population using opioids. The opioid stewardship programme consists of a variety of harmful lowering interventions or methods that are widely used to steer clear of the effects of prescription opioids, including abuse, improper use, addiction, and opioid disorders. Materials and Methods: This was a single-centre prospective interventional study conducted at Kovai Medical Centre and Hospital (a 1000-bed hospital with 18 operating theatres and 135 ICU beds) in the state of Tamil Nadu from April 2023 to September 2023 to analyse the impact of OSP. Results: A total of 471 patients were included in the analysis. The mean age of the study population was 53.71 years (SD: 14.40), and statistical significance was observed (p-value = 0.53). The average numerical pain rating scale was measured by ANOVA, and the difference was significant between different opioids. Statistically, no association was observed between opioids and side effects (p-value > 0.05). The prevalence rate of sleeping disturbances and drowsiness was higher with the use of both benzodiazepines and opioids. No significant difference was observed in the average morphine milligramme equivalent across departments, p-value>0.05. Conclusion: We conclude that a comprehensive opioid stewardship programme offers a rational enhancement of the use of opioids and helps recognise the risks associated with opioid use.
Keywords: Opioid; Opioid crisis; Opioid stewardship programme; Pain; Morphine